Sodium alginate gel electrolyte membrane and preparation method thereof, sodium alginate-based zinc composite material and aqueous zinc ion battery
By using sodium alginate gel electrolyte membrane in zinc ion batteries, the integrated structure is formed by electrochemical electroplating, the thermodynamic stability problem of zinc anode in water-based electrolyte is solved, the cycle performance and life of the battery are improved, and the cycle performance and life of the battery are achieved. Safe and environmentally friendly industrial production.
Patent Information
- Application Number
- CN202411425750.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-31
AI Technical Summary
The zinc anode has poor thermodynamic stability in the water-based electrolyte, resulting in side reactions and dendrites growth, affecting the utilization rate and life of the battery, and it is difficult for the prior art to maintain a stable zinc anode structure during long cycles.
Sodium alginate gel electrolyte membrane is used to grow in situ on the zinc surface by electrochemical plating to form a gel electrolyte membrane doped with zinc ions. Combined with zinc materials, an integrated structure is formed to avoid dendrites' growth and improve electrochemical performance.
The structural stability and electrochemical performance of zinc ion batteries during long-term cycles are achieved, and the utilization rate of zinc anode and the life of the battery are improved. At the same time, the process is simple, safe and environmentally friendly, and pollutant emissions are free.
Smart Images

Figure CN119230974A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a sodium alginate gel electrolyte membrane and a preparation method thereof, a sodium alginate-based zinc composite material, and an aqueous zinc ion battery. Background Art
[0002] The booming development of portable devices is mainly driven by wearable devices, such as wearable fitness trackers, wearable electrocardiogram monitors, smart watches and wearable blood pressure monitors. Currently, lithium-ion batteries are widely used in wearable devices due to their high energy density, long cycle stability and high energy efficiency. However, the organic electrolytes used in lithium-ion batteries are biotoxic and flammable and explosive, and are prone to fire or even explosion during use. Wearable devices are used in close contact with human skin and are difficult to get rid of when dangerous situations occur, posing serious safety hazards.
[0003] Zinc-ion batteries are gradually replacing lithium-ion batteries in the field of wearable electronic devices because of their green, safe, environmentally friendly nature and the use of water-based electrolytes. However, the thermodynamic stability of zinc anode materials in water-based electrolytes is poor. When the zinc anode comes into contact with water, side reactions will spontaneously occur, resulting in a significant decrease in the utilization rate of metallic zinc and the battery capacity. In addition, the zinc anode will also grow dendrites in the water-based electrolyte, which seriously affects the service life and coulombic efficiency of the zinc-ion battery.
[0004] In order to construct a stable zinc anode structure, various strategies such as solid zinc electrode and liquid electrolyte are used in the prior art to improve the electrochemical performance of zinc ion batteries by constructing a solid / electrolyte interface (SEI) layer on the zinc anode surface and optimizing the electrolyte components. However, the layer structure attached to the zinc anode surface is prone to separation during long-term cycling, which affects the long-cycle performance of zinc ions. It is urgent to provide a solution to improve the above problem. Summary of the invention
[0005] The invention aims to provide a sodium alginate-based gel electrolyte membrane and a preparation method thereof, a sodium alginate-based zinc composite material and an aqueous zinc ion battery.
[0006] In a first aspect, the present invention provides a method for preparing a sodium alginate gel electrolyte membrane, wherein a sodium alginate gel electrolyte membrane doped with zinc ions is in situ grown on a zinc surface by electrochemical plating in a sodium alginate gel solution.
[0007] The preparation method provided by the present invention does not require special equipment and is easy to carry out industrial-scale production. In addition, the prepared sodium alginate gel electrolyte membrane is closely combined with zinc by electroplating, thereby maintaining the structural stability and electrochemical performance stability of the battery during the long-term cycle. At the same time, the raw materials used in the present invention are cheap and the preparation process is simple. By controlling the parameters during electrochemical plating, the forming thickness of the sodium alginate gel electrolyte membrane can be effectively controlled, and it has good solubility, and the overall process is safe, environmentally friendly, and has no pollutant emissions.
[0008] Optionally, a high molecular polymer having a chain molecular structure is also dissolved in the sodium alginate gel solution, and the molecular weight of the high molecular polymer is 25-300000.
[0009] Optionally, the mass ratio of the high molecular weight polymer to the sodium alginate in the sodium alginate gel solution is (0.5-5):1.
[0010] Optionally, the concentration of sodium alginate in the sodium alginate gel solution is 2-20 mg / mL.
[0011] Optionally, the high molecular polymer includes one of polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyvinyl pyrrolidone, polyvinylidene fluoride and polyethylene glycol.
[0012] Optionally, the solvent of the sodium alginate gel solution includes deionized water.
[0013] Optionally, in a sodium alginate gel solution, a zinc foil is used as an anode and a thin film electrode is used as a cathode, and after electroplating for 5-20 minutes at a DC voltage of 0.5-4.0V, a sodium alginate gel electrolyte membrane in situ grown on the surface of the zinc foil is obtained.
[0014] Optionally, the zinc foil has a thickness of 10-100 μm.
[0015] Optionally, the thickness of the thin film electrode is 10-400 μm.
[0016] Optionally, the thin film electrode includes one of zinc foil, carbon paper, carbon cloth, copper foil, aluminum foil, and stainless steel foil.
[0017] In a second aspect, the present invention also provides a sodium alginate gel electrolyte membrane prepared by any of the above optional preparation methods.
[0018] In a third aspect, the present invention further provides a sodium alginate-based zinc composite material prepared by any of the above optional preparation methods, wherein zinc and the sodium alginate gel electrolyte membrane form an integrated structure.
[0019] Optionally, the discharge area specific capacity of the sodium alginate-based zinc composite material is 0.39-0.47 mAh / cm2 .
[0020] In a fourth aspect, the present invention further provides an aqueous zinc ion battery having a sodium alginate gel electrolyte membrane prepared by any of the above optional preparation methods, or having any of the above optional sodium alginate-based zinc composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The photos are of the sodium alginate gel electrolyte membranes prepared in Example 1 (A) and Example 2 (B) of the present invention;
[0022] Figure 2 The photos are of the sodium alginate-based zinc composite materials prepared in Example 1 (A) and Example 2 (B) of the present invention assembled into a flexible zinc ion battery;
[0023] Figure 3 The flexible zinc ion battery corresponding to Example 1 of the present invention is 0.1 mA / cm 2 The charge and discharge curves at the current density of ;
[0024] Figure 4 The flexible zinc ion battery corresponding to Example 2 of the present invention is 0.1 mA / cm 2 The charge and discharge curves at the current density. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0026] The present invention provides a method for preparing a sodium alginate gel electrolyte membrane, comprising in-situ growing a sodium alginate gel electrolyte membrane doped with zinc ions on a zinc surface by electrochemical plating in a sodium alginate gel solution. In fact, the bonding force between the sodium alginate gel electrolyte membrane and the zinc surface can be effectively improved by electroplating, and the structure and performance of the sodium alginate gel electrolyte membrane can be adjusted by adjusting the electroplating parameters.
[0027] Specifically, during the electroplating process, the surface of the zinc material loses electrons and generates divalent zinc ions on the surface. When the divalent zinc ions come into contact with the sodium alginate molecules, a cross-linking reaction occurs, thereby generating a gel electrolyte membrane containing zinc ions in situ on the zinc surface.
[0028] In fact, by integrating zinc and sodium alginate gel electrolyte membrane for in-situ electroplating, the interfacial contact can be effectively improved, thereby improving the transmission capacity of zinc ions between the electrolyte membrane and zinc. In addition, the structural stability between the electrolyte membrane and zinc can be improved to avoid relative slippage during deformation. At the same time, no external zinc salt is required during in-situ electroplating, and the formed zinc ion-doped sodium alginate gel electrolyte membrane can effectively inhibit the formation of zinc dendrites.
[0029] Specifically, the concentration of sodium alginate in the sodium alginate gel solution is 2-20 mg / L. In fact, when the sodium alginate gel electrolyte membrane is electroplated, if the sodium alginate concentration is too low, a larger electroplating voltage and a longer electroplating time are required, which is not conducive to improving the overall efficiency. When the sodium alginate concentration is too high, it is easy to form an overly thick electrolyte membrane on the zinc surface, which is not conducive to controlling the thickness and structure of the sodium alginate gel electrolyte membrane.
[0030] In some embodiments, a polymer having a chain molecular structure is also dissolved in the sodium alginate gel solution, and the molecular weight of the polymer is 25-300000. In fact, during the electroplating process, the polymer can cross-link with the sodium alginate molecules, thereby effectively improving the film-forming property and mechanical properties of the sodium alginate gel electrolyte membrane.
[0031] Specifically, when a high molecular polymer is also dissolved in the sodium alginate gel solution, the high molecular polymer includes one of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylamide (PAM), polyvinyl pyrrolidone (PVP), polyvinylidene fluoride (PVDF) and polyethylene glycol (PEG).
[0032] In fact, the mass ratio of polymer to sodium alginate in the sodium alginate gel solution is (0.5-5):1. By adjusting the amount of polymer, the effect of polymer on the performance of gel electrolyte membrane can be adjusted. Specifically, when the amount of polymer is too low, it is difficult to improve the mechanical properties of the electrolyte membrane, while when the amount of polymer is too high, it will affect the transfer rate of zinc ions in the electrolyte membrane, thereby affecting the electrochemical properties of the electrolyte membrane.
[0033] Specifically, the solvent in the sodium alginate gel solution includes deionized water. In fact, the solvent in the sodium alginate gel solution must be able to completely dissolve the sodium alginate and the high molecular polymer.
[0034] In some embodiments, the preparation method of the sodium alginate gel electrolyte membrane provided by the present invention comprises: in a sodium alginate gel solution, using zinc foil as an anode and a thin film electrode as a cathode, and electroplating for 5-20 minutes at a DC voltage of 0.5-4.0V to obtain a sodium alginate gel electrolyte membrane grown in situ on the surface of the zinc foil.
[0035] In fact, by adjusting the DC voltage during electroplating and controlling the electroplating time, the structure and performance of the formed gel electrolyte membrane can be effectively adjusted. In fact, those skilled in the art can arbitrarily adjust the electroplating voltage and electroplating time within a suitable range to synthesize gel electrolyte membranes with similar morphology, the difference being the difference in electrochemical and mechanical properties.
[0036] In fact, during electroplating, the thin film electrode is used to receive electrons from the zinc foil anode, so the thin film electrode is also a key factor affecting the quality of electroplating film, so the thin film electrode is made of a material with good conductivity. Specifically, considering the economic cost and the convenience of raw materials, the thin film electrode can be one of graphite paper, zinc foil, carbon paper, carbon cloth, copper foil, aluminum foil, and stainless steel foil.
[0037] In fact, the thickness of the zinc foil during electroplating is 10-100 μm, and the thickness of the thin film electrode is 10-400 μm. The zinc foil is configured in a thin sheet shape, which is conducive to the formation of the gel electrolyte membrane on the surface of the zinc foil. In fact, the zinc foil can also be configured in a cylindrical shape or any other shape, which can form the gel electrolyte membrane on the surface during electroplating.
[0038] Specifically, the present invention also provides a sodium alginate gel electrolyte membrane prepared by any of the above preparation methods, the electrolyte membrane comprising a sodium alginate gel network cross-linked under the action of zinc ions, and zinc ions doped in the gel network.
[0039] In fact, when a high molecular polymer is dissolved in the sodium alginate gel electrolyte used in preparing the sodium alginate gel electrolyte membrane, the prepared gel electrolyte also includes a high molecular polymer network cross-linked with the sodium alginate gel network.
[0040] Similarly, the present invention also provides a sodium alginate-based zinc composite material prepared by any of the above preparation methods, wherein zinc and the sodium alginate gel electrolyte membrane are integrated by in-situ electroplating, which is beneficial to improving the structural stability and interface bonding performance of the zinc material and the sodium alginate gel electrolyte membrane.
[0041] In fact, after the sodium alginate-based zinc composite material provided by the present invention is used as the negative electrode material and combined with the manganese dioxide positive electrode material to form a flexible zinc ion battery, the discharge area specific capacity of the flexible zinc ion battery is measured to be 0.39-0.47 mAh / cm2 .
[0042] Similarly, the present invention also provides an aqueous zinc ion battery, wherein the negative electrode material has a sodium alginate gel electrolyte membrane prepared by any of the above preparation methods, or the aqueous zinc ion battery has any of the above-mentioned sodium alginate-based zinc composite materials as the negative electrode.
[0043] Example 1
[0044] This embodiment 1 provides a method for preparing a sodium alginate-based zinc composite material, comprising the following steps:
[0045] S1. Stir and dissolve sodium alginate powder in deionized water to prepare a sodium alginate gel solution with a concentration of 10 mg / mL, and add 70 mL of the sodium alginate gel solution into a beaker with a volume of 100 mL for later use;
[0046] S2. Cut the zinc foil with a thickness of 20 μm to 2 cm in length × 2.5 cm in width and the graphite paper with a thickness of 330 μm to 3 cm in length × 3 cm in width, connect the positive electrode of the DC power supply to the zinc foil through an electric clamp, and connect the negative electrode to the graphite paper through an electric clamp, set the voltage of the DC power supply to 1.5 V, and perform constant voltage electroplating for 5 minutes to obtain a sodium alginate-based zinc composite material.
[0047] Example 2
[0048] This embodiment 2 provides a method for preparing a sodium alginate-based zinc composite material, comprising the following steps:
[0049] S1. Add polyvinyl alcohol (PVA) with a molecular weight of 20,000 into deionized water, stir for 2 h in a 95°C water bath until completely dissolved and clear, then add sodium alginate powder in a mass ratio of 1:1 to polyvinyl alcohol and stir to dissolve, adjust the concentration of polyvinyl alcohol and sodium alginate to 10 mg / mL to obtain a sodium alginate gel solution;
[0050] S2. Cut the zinc foil with a thickness of 20 μm to 2 cm in length × 2.5 cm in width and the graphite paper with a thickness of 330 μm to 3 cm in length × 3 cm in width, connect the positive electrode of the DC power supply to the zinc foil through an electric clamp, and connect the negative electrode to the graphite paper through an electric clamp, set the voltage of the DC power supply to 1.5 V, and perform constant voltage electroplating for 5 minutes to obtain a sodium alginate-based zinc composite material.
[0051] Performance Testing
[0052] The sodium alginate-based zinc composite materials prepared in Example 1 and Example 2 are photographed. Figure 1 As shown, from Figure 1It can be seen from A in Example 1 that since no high molecular weight polymer is added, the film-forming performance of the sodium alginate gel electrolyte membrane on the zinc foil surface is affected, and the discharge capacity decreases. Figure 1 From B in the figure, it can be seen that the gel electrolyte membrane in Example 2 has good film-forming performance and a smooth and flat surface.
[0053] The sodium alginate-based zinc composite material prepared in Example 1 and Example 2 was used as the negative electrode and solid electrolyte, and assembled with the manganese dioxide positive electrode to support the flexible zinc ion battery and photographed. Figure 2 As shown in A and B, Figure 2 It can be seen from B that the use of Figure 1 A sodium alginate-based zinc composite material (Example 2, Figure 1 B) When applied to both sides of the manganese dioxide positive electrode as the negative electrode and electrolyte of the zinc ion battery, they have good contact with the manganese dioxide positive electrode. Since the film is very uniform and flat, the battery as a whole also looks uniform and flat. Figure 2 It can be seen from A that the use of Figure 1 The sodium alginate-based zinc composite material (Example 1, Figure 1 A) When they are respectively applied to both sides of the manganese dioxide positive electrode as the negative electrode and electrolyte of the zinc ion battery, they have general contact with the manganese dioxide positive electrode. Due to the poor mechanical properties of the membrane, the membrane will flow and fall under the influence of gravity, resulting in uneven battery thickness and affecting battery performance.
[0054] The flexible zinc ion batteries prepared in Example 1 and Example 2 were heated at 0.1 mA / cm 2 The charge and discharge tests were carried out at a current density of Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It can be seen Figure 2 A battery (Example 1) at 0.1 mA / cm 2 The first discharge area specific capacity at a current density of 0.39 mAh / cm 2 , and the charging and discharging platform is not very obvious. Due to the poor contact between the positive and negative electrodes, there is a large polarization during the battery charging and discharging process. Figure 2 B battery (Example 2) at 0.1 mA / cm 2 The first discharge area specific capacity at a current density of 0.47 mAh / cm 2 , and there is a more obvious charge and discharge platform, and the capacity is also improved, indicating that adding polymers is more helpful in improving the performance of electroplated gel electrolyte membranes and battery performance than not adding polymers.
[0055] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for preparing a sodium alginate gel electrolyte membrane, characterized in that: A sodium alginate gel electrolyte membrane doped with zinc ions is in-situ grown on a zinc surface by electrochemical plating in a sodium alginate gel solution.
2. The preparation method according to claim 1, characterized in that: A high molecular polymer with a chain molecular structure is also dissolved in the sodium alginate gel solution, and the molecular weight of the high molecular polymer is 25-300000.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the high molecular weight polymer to the sodium alginate in the sodium alginate gel solution is (0.5-5):1; and / or, the concentration of sodium alginate in the sodium alginate gel solution is 2-20 mg / mL; And / or, the high molecular polymer includes one of polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyvinyl pyrrolidone, polyvinylidene fluoride and polyethylene glycol; And / or, the solvent of the sodium alginate gel solution includes deionized water.
4. The preparation method according to any one of claims 1 to 3, characterized in that: include: In a sodium alginate gel solution, a zinc foil is used as an anode and a thin film electrode is used as a cathode. After electroplating for 5-20 minutes at a DC voltage of 0.5-4.0V, a sodium alginate gel electrolyte membrane in situ grown on the surface of the zinc foil is obtained.
5. The preparation method according to claim 4, characterized in that: The thickness of the zinc foil is 10-100 μm; And / or, the thickness of the thin film electrode is 10-400 μm; And / or, the thin film electrode includes one of graphite paper, zinc foil, carbon paper, carbon cloth, copper foil, aluminum foil, and stainless steel foil.
6. A sodium alginate gel electrolyte membrane prepared by the preparation method according to any one of claims 1 to 5.
7. A sodium alginate-based zinc composite material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: Zinc and sodium alginate gel electrolyte membrane are formed into an integrated structure by in-situ electroplating.
8. The sodium alginate-based zinc composite material according to claim 7, characterized in that: The discharge area specific capacity of the sodium alginate-based zinc composite material is 0.39-0.47 mAh / cm 2 .
9. An aqueous zinc ion battery, characterized in that: A sodium alginate gel electrolyte membrane prepared by the preparation method according to any one of claims 1 to 5, or a sodium alginate-based zinc composite material according to any one of claims 7 to 8.
Citation Information
Cited By
Modified sodium alginate cross-linked hydrogel electrolyte as well as preparation method and application thereof
CN119978260A
